O6D.2 Evidence of dna methylation changes by carbon nanotubes in a translational study design. (April 2019) - Ghosh, Manosij; Öner, Deniz; Godderis, Lode; Hoet, Peter
Abstract : Introduction: While studies have addressed genotoxic effects of CNT, only limited information are available on epigenetic effects. We designed a study to investigate DNA methylation alterations in vitro, in vivo and in occupationally exposed workers. Material and methods: In vitro studies were performed in 16-HBE and THP-1 cells. For the in vivo study, BALB/c mice were administered intratracheally with single-wall CNT (SWCNTs) and multi-wall (MWCNTs) at high (2.5 mg/kg) and low (0.25 mg/kg) doses. For the cross sectional study, 24 workers exposed to aggregates of MWCNT of 500 nm–100 µm with concentrations of 4.6–42.6 µg/m3 and 43 unexposed referents were recruited. Global DNA methylation and demethylation patterns were analysed by LC-MS/MS. Methylation of specific genes was measured by Pyromark 24® (Qiagen). Genome-wide assessment of DNA methylation was performed with Infinium HumanMethylation450 BeadChip Array. Results: In general, we did not find global DNA methylation alteration for both CNTs. In 16-HBE cells, differentially methylated and expressed genes (MWCNTs>SWCNTs) from p53 signalling, DNA damage repair and cell cycle pathways were observed. In THP-1 cells, CNTs induced promoter-specific methylation of genes involved in several signaling cascade, vascular endothelial growth factor and platelet activation pathways. In lungs of BALB/c mice CNTs affected methylation of ATM gene. Finally, analysis of gene-specific DNA methylation in exposed workers revealed significant changes for DNMT1, ATM, SKI, and HDAC4 promoter CpGs. Conclusions: Epigenetic changes seem to occur at sub cyto-genotoxic concentrations in vitro . Alteration in DNA methylation pattern could be a natural reaction of cells but could also silence critical genes and reprogram cellular functions.